2011
DOI: 10.1038/jcbfm.2011.85
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol Vitamin E Protects against Preclinical Canine Ischemic Stroke by Inducing Arteriogenesis

Abstract: Vitamin E consists of tocopherols and tocotrienols, in which a-tocotrienol is the most potent neuroprotective form that is also effective in protecting against stroke in rodents. As neuroprotective agents alone are insufficient to protect against stroke, we sought to test the effects of tocotrienol on the cerebrovascular circulation during ischemic stroke using a preclinical model that enables fluoroscopy-guided angiography. Mongrel canines (mean weight = 26.3 ± 3.2 kg) were supplemented with tocotrienol-enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 38 publications
0
53
0
1
Order By: Relevance
“…Rescue of miR-29b against stroke-induced loss was also achieved by the 12-lipoxygenase inhibitor a-tocotrienol, which is a form on natural vitamin E that might be used in nutritional intervention against stroke. 7,17,30,33 During stroke, arachidonic acid is mobilized from the membrane of GSH-deficient cells and feeds the 12-lipoxygenase pathway triggering the production of reactive lipid metabolites, which function as mitochondrial toxin. 39,40 Our laboratory was the first to report a central role of 12-lipoxygenase in regulating stroke outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rescue of miR-29b against stroke-induced loss was also achieved by the 12-lipoxygenase inhibitor a-tocotrienol, which is a form on natural vitamin E that might be used in nutritional intervention against stroke. 7,17,30,33 During stroke, arachidonic acid is mobilized from the membrane of GSH-deficient cells and feeds the 12-lipoxygenase pathway triggering the production of reactive lipid metabolites, which function as mitochondrial toxin. 39,40 Our laboratory was the first to report a central role of 12-lipoxygenase in regulating stroke outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…28 MicroRNA Expression Assay from Laser-Captured Microdissected Somatosensory Cortex of Brain Tissue Laser microdissection and pressure catapulting was performed using the microlaser system from PALM Microlaser Technologies AG (Bernreid, Germany) as described. 17,21,26,27,29,30 Briefly, mice were euthanized immediately after MRI imaging and coronal slices of brain tissue were collected using a mouse brain matrix. OCT embedded in slices were subsequently cut in 12-mm-thick sections on a Leica CM 3050S cryostat (Leica Microsystems, Wetzlar, Germany).…”
Section: Magnetic Resonance Imaging and Infarct Volume Determinationmentioning
confidence: 99%
“…Given by oral gavage for several weeks before the ischemic insult, a-tocotrienol reduced infarct size in rats[19]. It is not known what the time window would be for using a-tocotrienol in acute stroke, but it also reduced severity of stroke injury when dosed chronically in canines, suggesting it may have utility in secondary stroke prevention[57]. In addition to inhibiting 12/15-LOX and a general antioxidant effect, a-tocotrienol may also protect by targeting Multidrug Resistance-Associated Protein 1[58].…”
Section: Targeting 12/15-lox In Rodent Models Of Stroke: Gene Knockoumentioning
confidence: 99%
“…A series of studies in our laboratory have demonstrated potent in vitro as well as in vivo neuroprotective properties of aTE against neurodegeneration and stroke (5,(10)(11)(12)(13)(14)(15). Recently, we concluded a randomized, blinded, preclinical trial in canines where orally supplemented TE proved to be substantially effective in protecting against strokeinduced brain lesions as evaluated by high resolution MRI (10). In particular, TE has been shown to significantly reduce hemispherical infarct volume and prevent loss of white matter fiber tract connectivity in canines subject to MCA occlusion (10).…”
Section: Introductionmentioning
confidence: 99%